The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ma13010157
|View full text |Cite
|
Sign up to set email alerts
|

Water Droplet Erosion of Wind Turbine Blades: Mechanics, Testing, Modeling and Future Perspectives

Abstract: The problem of erosion due to water droplet impact has been a major concern for several industries for a very long time and it keeps reinventing itself wherever a component rotates or moves at high speed in a hydrometer environment. Recently, and as larger wind turbine blades are used, erosion of the leading edge due to rain droplets impact has become a serious issue. Leading-edge erosion causes a significant loss in aerodynamics efficiency of turbine blades leading to a considerable reduction in annual energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 122 publications
1
28
0
Order By: Relevance
“…There are many ways to recreate the conditions of a wind turbine blade in the field within laboratory conditions and there have been some issues with cross referencing results from different methodologies [4,11,12]; however, the technique that replicates the conditions closest would be a whirling arm erosion rig (WARER) as stated by the DNVGL recommended practice [13]. The rig that was used for this investigation was built in the University of Strathclyde in the tribology laboratory to artificially simulate turbine blade conditions [14,15].…”
Section: Testing Apparatusmentioning
confidence: 99%
“…There are many ways to recreate the conditions of a wind turbine blade in the field within laboratory conditions and there have been some issues with cross referencing results from different methodologies [4,11,12]; however, the technique that replicates the conditions closest would be a whirling arm erosion rig (WARER) as stated by the DNVGL recommended practice [13]. The rig that was used for this investigation was built in the University of Strathclyde in the tribology laboratory to artificially simulate turbine blade conditions [14,15].…”
Section: Testing Apparatusmentioning
confidence: 99%
“…In some failure analyses of a 52.3 m composite wind turbine blade, it was found that accumulated delamination of unidirectional composites in the spar cap was one of the main reason for the blade collapse [ 21 , 22 ]. Delamination often takes place due to manufacturing process or in-service loads, or even due to water droplet erosion [ 23 ]. Hence, delamination characterization is essential to study the damage tolerance in composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Wear fatigue failure analysis based on Springer model requires coating and substrate speed of sound measurements as input material parameters. The model does not account for a very high-rate transient pressure build-up and the viscoelastic effects are frequency dependent for the materials involved [16][17][18]. The main objective of this research is to fully apply the Springer model but considering the effect of the viscoelastic stress-strain development during the impact event in the LEP multilayer system by means of the appropriate frequency range definition for the coating layer impedance characterization.…”
Section: Introductionmentioning
confidence: 99%